2018
DOI: 10.3389/fmars.2017.00433
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model for Projecting Coccolithophorid Growth, Calcification and Photosynthetic Carbon Fixation Rates in Response to Global Ocean Change

Abstract: Temperature, light and carbonate chemistry all influence the growth, calcification and photosynthetic rates of coccolithophores to a similar degree. There have been multiple attempts to project the responses of coccolithophores to changes in carbonate chemistry, but the interaction with light and temperature remains elusive. Here we devise a simple conceptual model to derive a fit equation for coccolithophorid growth, photosynthetic and calcification rates in response to simultaneous changes in carbonate chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
64
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 68 publications
9
64
2
Order By: Relevance
“…However, Paasche and Brubak (1994) observed that calcification is less strongly curtailed than photosynthesis under low light conditions, so perhaps high calcification relative to growth in winter could lead to heavier coccolith weights in that part of the seasonal cycle. Interestingly, this would contrast with a recent synthesis of results for another coccolithophore, Gephyrocapsa oceanica, in which optimal light for calcification was found to be slightly higher than for photosynthesis or growth (Gafar et al, 2018), emphasising that the sensitivities of these processes may be organism and possibly even strain specific. Smith et al (2012) previously documented a reduction in coccolith calcification of E. huxleyi coccospheres during the summer months in the Bay of Biscay, but advised caution in associating this with light intensity because calcification rates may not necessarily covary with the amount of calcite content per coccolith.…”
Section: Seasonal Variability In Coccolith Calcificationcontrasting
confidence: 75%
“…However, Paasche and Brubak (1994) observed that calcification is less strongly curtailed than photosynthesis under low light conditions, so perhaps high calcification relative to growth in winter could lead to heavier coccolith weights in that part of the seasonal cycle. Interestingly, this would contrast with a recent synthesis of results for another coccolithophore, Gephyrocapsa oceanica, in which optimal light for calcification was found to be slightly higher than for photosynthesis or growth (Gafar et al, 2018), emphasising that the sensitivities of these processes may be organism and possibly even strain specific. Smith et al (2012) previously documented a reduction in coccolith calcification of E. huxleyi coccospheres during the summer months in the Bay of Biscay, but advised caution in associating this with light intensity because calcification rates may not necessarily covary with the amount of calcite content per coccolith.…”
Section: Seasonal Variability In Coccolith Calcificationcontrasting
confidence: 75%
“…Tables 1, 2 and 3. Species specific differences in response to changing carbonate chemistry, temperature and light were assessed by comparing the above fit to that recently produced for Gephyrocapsa oceanica (Gafar et al, 2018).…”
Section: Temperature and Light Transformationsmentioning
confidence: 99%
“…While our fit equation has previously explained variability in lab experiments quite well (Gafar et al, 2018), natural systems are much more complex, with the interactions of dozens of variables including temperature, light, nutrients, predation and competition all influencing productivity (Behrenfeld, 2014). As such we wanted to examine how our, relatively simple, equation…”
Section: Global Calcium Carbonate Production Potentialmentioning
confidence: 99%
See 2 more Smart Citations